Illness representations and psychological distress in Indian patients with cancer: does being aware of one's cancer diagnosis make a difference?. Issue 12 (27th May 2015) - Chittem, Mahati; Norman, Paul; Harris, Peter R.
Abstract: Background: This study applied the Common Sense Model of illness representations to understand the psychological reactions of Indian patients with cancer who report being aware or unaware of their cancer diagnosis. Methods: Adult Indian patients with cancer ( N  = 329) were asked about their understanding of their illness (to assess awareness of a cancer diagnosis), and then completed the Brief Illness Perception Questionnaire and the Hospital Anxiety Depression Scale. Results: Patients who reported being unaware of their cancer diagnosis (54.1%) experienced higher levels of anxiety and depression. After controlling for awareness, education, income, cancer symptoms, and cancer stage, illness perceptions accounted for significant amounts of variance in anxiety (∆ R 2  = 0.42) and depression (∆ R 2  = 0.33). Illness coherence mediated the relationship between awareness of a cancer diagnosis and anxiety. Moderated regression analyses indicated that several relationships between illness perceptions and anxiety/depression were stronger among patients who reported being unaware of their cancer diagnosis. Conclusions: The Common Sense Model provides a useful framework for explaining the psychological reactions of Indian patients with cancer to their illness, particularly for those who report being unaware of their cancer diagnosis. Copyright © 2015 John Wiley & Sons, Ltd.